The impact of corporate social responsibility (CSR) activities on British American Tobacco (BAT) from the public's perspective / Nor Raihana Asmar Mohd Noor - Mohd Noor, Nor Raihana Asmar (2013)
Corporate Social Responsibility (CSR) plays an important role to the public. Organizations should emphasize more on CSR activities not only focusing to achieve higher profit for the organization. In addition, they must also be concerned about other ethical elements such as workplace, marketplace, community and environment in ensuring the sustainability of the organization whilst strengthening the intangible value of the company such as corporate image, customer's purchasing intention, attracting potential employees, loyalty and commitment from customers. This study aims to (i) examine the level of awareness of the public on British American Tobacco (BA I)'s CSR activities from demographic perspective; (ii) determine the relationship between community activities and impact of CSR on BAT; (iii) determine the relationship between environment activities and impact of CSR on BAT; (iv) determine the relationship between workplace activities and impact of CSR on BAT; (v) determine the relationship between marketplace activities and impact of CSR on BAT. The scope of this study covers the public in Shah Alam, Selangor. This study employs a cross sectional survey to investigate the impact of CSR activities on BAT from the public's perspective. This study uses several statistical techniques such as the descriptive statistics, correlations and regression. The results of the study show that there are significant relationship between community and workplace activities and the impact of CSR activities, negative relationship between marketplace and the impact of CSR activities and no relationship between environment activities and the impact of CSR.